US based NGOs in international development: financial and economic determinants of survival - Nunnenkamp, Peter; Öhler, Hannes; Schwörer, Tillmann (World development, 2013)
The accountability of non-governmental organizations (NGOs) has various dimensions. From an economic perspective, official financiers, private donors as well as aid recipients could expect more charitable output from NGOs, if less efficient organizations were squeezed out of international development activities. We consider administrative overheads as an important aspect of NGO efficiency. Our empirical analysis focuses on the effects of administrative overheads, public funding and the interrelations between these two factors on the probability of “market” exit for almost 900 US based NGOs with overseas aid activities since the mid-1980s. We find that larger administrative overheads increase the probability of exit for NGOs receiving any public funding. However, this effect weakens with increasing shares of public funding of NGOs.
Gesehen am 29.11.2021